2015
DOI: 10.3945/an.114.007377
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell–Mediated Protection of the Mammary Gland and the Infant during Breastfeeding

Abstract: Breastfeeding has been regarded first and foremost as a means of nutrition for infants, providing essential components for their unique growth and developmental requirements. However, breast milk is also rich in immunologic factors, highlighting its importance as a mediator of protection. In accordance with its evolutionary origin, the mammary gland offers via the breastfeeding route continuation of the maternal to infant immunologic support established in utero. At birth, the infant's immune system is immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 98 publications
(143 reference statements)
4
97
0
14
Order By: Relevance
“…Past the colostral stage, human BM contains *10 3 -10 4 leukocytes per milliliter, [21][22][23][24][25] and it has been shown recently that as BM matures over the first month, the neutrophil concentration increases. 26 Importantly, various animal studies have demonstrated that maternal leukocytes in BM are FIG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past the colostral stage, human BM contains *10 3 -10 4 leukocytes per milliliter, [21][22][23][24][25] and it has been shown recently that as BM matures over the first month, the neutrophil concentration increases. 26 Importantly, various animal studies have demonstrated that maternal leukocytes in BM are FIG.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Given that BM contains *10 2 -10 5 leukocytes per milliliter, it can be estimated that breastfed infants ingest *10 5 -10 8 maternal leukocytes daily. 25 Varied cell classification methods have found macrophages and neutrophils to dominate in colostrum (40-50% of total leukocytes, respectively), followed by lymphocytes (5-10%), although very few studies of BM composition beyond early lactation exist. 21 Colostrum exhibits a significantly higher cell count than mature milk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, flow cytometric analysis of HM cells has revealed that the majority of lactocytes and stem cells contain the leptin protein [22]. Given that lactocytes are the dominant cell type in mature whole HM when both the mother and infant are healthy [1,48,49,53,54], it is likely that lactocytes contribute significantly to HM leptin levels. Indeed, the cellular fraction of HM can constitute a significant portion of milk, comparable to its skim and fat fractions [1,31].…”
Section: Discussionmentioning
confidence: 99%
“…La leche materna protege de forma activa y pasiva al lactante, gracias a su riqueza en inmunoglobulinas, lactoferrina, lisozima, citoquinas y otros numerosos factores inmunológicos, como leucocitos maternos, que proporcionan inmunidad activa y promueven el desarrollo de la inmunocompetencia del bebé (68). En este sentido, se han descrito importantes hallazgos a través de diversos estudios, al mostrar el papel protector que ejerce la LM ante diversas enfermedades.…”
Section: Lm E Infecciones Del Niñounclassified